RDA: A Coq Library to Reason about Randomised Distributed Algorithms in the Message Passing Model - A. Fontaine; A. Zemmari (Scientific Annals of Computer Science)
Distributed algorithms have received considerable attention and were studied intensively in the past few decades. Under some hypotheses on the distributed system, there is no deterministic solution to certain classical problems. Randomised solutions are then needed to solve those problems. Probabilistic algorithms are generally simple to formulate. However, their analysis can become very complex, especially in the field of distributed computing.